2016
DOI: 10.4274/turkderm.35336
|View full text |Cite
|
Sign up to set email alerts
|

Classic Kaposi’s sarcoma: The clinical, demographic and teratment characteristics of seventy-four patients

Abstract: Background and Design: Classic Kaposi's sarkoma (CKS) is a rare disease, generally seen across Mediterranean and the Middle East region. It's an angioproliferative disorder associated with human herpes virus-8 infection. There is a few data on epidemiology and clinical characteristics among Turkish patients with CKS. This study aims to evaluate epidemiologic, clinical characteristics and treatment results in patients with the diagnosis of CKS in Zonguldak. Materials and Methods: We retrospectively evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
3
5
2
Order By: Relevance
“…During the follow-up period, which ranged from 3 months up to 35 years, recurrence occurred in approximately one third of our patients. Demirel et al [12] reported local recurrence in 34% of patients, similar rates as in our study. Long-term follow-up should be necessary for local or distant recurrence.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…During the follow-up period, which ranged from 3 months up to 35 years, recurrence occurred in approximately one third of our patients. Demirel et al [12] reported local recurrence in 34% of patients, similar rates as in our study. Long-term follow-up should be necessary for local or distant recurrence.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that the risk of lymphohematological malignancies in KS patients is 20 times higher than that of the normal population [25]. We found a second primary malignancy in 21 (23%) patients, whereas Su et al [6] and Demirel et al [12] found second primary malignancies in 2 (11.1%) patients (colon and stomach) and 3 (3.7%) (2 colon and 1 prostate) patients, respectively. Although commonly observed second primary malignancies such as prostate, hematological and gastrointestinal cancers may be expected in the older population, the total second primary malignancy rate (23%) was higher than in previous reports [26].…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations